2015
DOI: 10.3390/toxins7020478
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between the Basic Replicon and the Kis-Kid Maintenance System of Plasmid R1: Modulation by Kis Antitoxin Levels and Involvement in Control of Plasmid Replication

Abstract: kis-kid, the auxiliary maintenance system of plasmid R1 and copB, the auxiliary copy number control gene of this plasmid, contribute to increase plasmid replication efficiency in cells with lower than average copy number. It is thought that Kis antitoxin levels decrease in these cells and that this acts as the switch that activates the Kid toxin; activated Kid toxin reduces copB-mRNA levels and this increases RepA levels that increases plasmid copy number. In support of this model we now report that: (i) the K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Mean data were taken as the relative expression levels of the proteins. Band densitometry was determined using Quantity One v.4.6.3 software (Bio-Rad, Berkeley, CA) as previously described (Molina-García and Giraldo, 2014 ; López-Villarejo et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mean data were taken as the relative expression levels of the proteins. Band densitometry was determined using Quantity One v.4.6.3 software (Bio-Rad, Berkeley, CA) as previously described (Molina-García and Giraldo, 2014 ; López-Villarejo et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…The kis/kid (killing suppression/killing determinant) type II TA system (pemI/pemK in plasmid R100 is identical to kis/kid) is encoded adjacent to the RepFII replicon of plasmid R1 and represents an example where the Kid (PemK) toxin is a sequence-specific RNase, thereby inhibiting translation of cellular mRNAs (53). It has also been shown that in case of a too-low-copy-number state before cell division, the Kid toxin can not only inhibit cell growth and division, but also stimulate plasmid replication by specifically inactivating the mRNA encoding the negative regulator CopB (26,54,55). The Kis/Kid type II TA system belongs to the MazEF superfamily (MazF CDD protein domain family: cl00995).…”
Section: Toxin-antitoxin Modules: Deadly Partners For Stable Maintenancementioning
confidence: 99%
“…Plasmid maintenance linked to the coordination of TAs with plasmid replication was initially reported by the Diaz-Orejas laboratory on the kis-kid TA encoded by plasmid R1 ( Ruiz-Echevarría et al, 1995a , b ), and further analyzed ( Pimentel et al, 2005 ; López-Villarejo et al, 2012 , 2015 ). Additional work revealed a further coordination of the kis-kid TA with cell cycle functions ( Pimentel et al, 2014 ).…”
Section: Functional Overlaps Between Chromosomal and Plasmid-encoded mentioning
confidence: 99%